A review of hydro-pneumatic and flywheel energy storage for hydraulic systems. Issue 2 (4th May 2018) - Cronk, Paul M.; Van de Ven, James D.
Abstract: This review will consider the state-of-the art in the storage of mechanical energy for hydraulic systems. It will begin by considering the traditional energy storage device, the hydro-pneumatic accumulator. Recent advances in the design of the hydraulic accumulator, as well as proposed novel architectures will be discussed. The review will continue with a discussion of energy storage flywheels. This will include recent advances in flywheel design and the properties of flywheels, particularly when compared to accumulators, as applied to hydraulic systems. These differences necessitate a discussion of the hydraulic system architectures used to incorporate flywheels, which will cover the various methods that have been proposed for utilising energy storage flywheels in hydraulic systems. The review will conclude by highlighting some of the unanswered questions in this area of engineering research and design.